Effect of Weed Management Practices on Citrus Growth and Cost of Production at Young Mandarin Orchard in Palpa, Nepal - Deepa Parajuli; Hom Nath Giri; Mamta Adhikari; Bidya Ojha; Astha Pokharel; Anusuya Aaradhana Panthee (International Journal of Fruit Science)
Although citrus cultivation has a comparative advantage in subtropical climates, meeting the increasing demand is challenging, primarily due to weed pressure contributing 25–33% yield loss. Henceforth, to assess the efficiency of weed management methods, enhance plant growth, and analyze economic treatment costs, research was conducted in a three-year-old mandarin (Citrus reticulata Blanco.) orchard at Citrus Development Center, Tansen, Palpa, in 2022. The experiment was designed in a single factorial randomized complete block design with five treatments: plastic mulch, organic mulch, herbicide, hand weeding, and a control. Fourteen weed species were identified, and the highest weed density was of sedges (45%). Results of the study showed that plastic mulch was an efficient method providing lower average weed diversity (1.7); weed density in all days after treatment (DAT) (0.5, 0.6, 1.9, 6.6, and 1.1 m−2); and weed dry weight at 15, 30, and 45 DAT (0.1, 0.3, and 0.4 gm−2). Plastic mulch observed with higher weed control efficiency (93.9, 87.1, 93.1, 91.8, and 93.4%) and weed control index (89.6%, 85.8%, 93.8%, 90.8%, and 96.35%) in all DAT. Whereas, the weed persistence index was lower in herbicide-treated plots at 30 (0.73), 45 (0.44), and 75 (0.24) DAT. Herbicide-treated plots showed the highest increment in crop growth parameters of plant height (33.7%) and plant canopy cover volume (180.8%) and were also the most economical with the lower annual treatment cost (NPR 210 thousand/ha). The superior plant growth, higher weed control, and lower cost proved herbicide treatment as an effective weed control method. However, plastic mulch, with outcomes resembling herbicide, can be a sustainable approach for weed control.